User experience evaluation of mobile AR services - Irshad, S. (Association for Computing Machinery, 2014)
Mobile Augmented Reality (MAR) is state-of-the-art technology that has modernized the way of accessing and interacting with information thus invoking new experiences for users all around the world. However User Experience (UX) evaluation for mobile AR is still a widely unexplored area. In order to identify the potential problems faced by the end users while using MAR applications, it is important to evaluate the UX of current Mobile AR service. This paper narrates the findings and analysis from a pilot study. We report a cross-sectional survey for evaluating the user experience of latest mobile AR applications. A framework of qualities related to user experience is applied on the acquired results to understand and articulate different aspects of UX. The outcomes show a positive attitude of users towards mobile AR services. The results help in considering key acceptance issues and potential user expectations in the development of future mobile AR services. Copyright 2014 ACM.